A Polynomial Synthesis Approach to Design and Control an LCL-Filter-Based PWM Rectifier with Extended Functions Validated by SIL Simulations - Rosa Iris Viera Díaz; Ciro Nuñez; Nancy Visairo Cruz; Juan Segundo Ramírez (Energies, 2023)
Controlling a PWM rectifier can be challenging due to the bilinear nature of its averaged model. This paper introduces the use of the Butterworth approach to design and control an LCL-filter-based PWM rectifier with power quality functions. By leveraging the linear part of the system, this approach reduces the number of variables involved in the control scheme. The rectifier is designed and controlled in a concatenated manner to ensure proper performance even during demanding power-quality events. The uniqueness of this approach lies in the fact that a fourth-order model can be regulated by using solely three-state variables and linear techniques founded on Butterworth polynomial synthesis. This approach differs from previous methods in that it does not employ nonlinear controllers, dq transformations, or double control loops. Hence, this divergent approach contributes to the simplification of power converter design and control through the application of the same polynomial synthesis, besides enhancing system operation in demanding scenarios. Extensive SIL simulations of a 1 kW, 220 Vrms PWM rectifier using the OPAL-RT-1400 platform were conducted to demonstrate the feasibility of the proposed controller. The selected tests reveal the validity of this proposal even when the PWM rectifier faces multiple power quality events simultaneously.